2011
DOI: 10.1038/aps.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

High cholesterol diet increases osteoporosis risk via inhibiting bone formation in rats

Abstract: Aim: To investigate the effects of high cholesterol diet on the development of osteoporosis and the underlying mechanisms in rats. Methods: Female Sprague-Dawley rats were randomly separated into 3 groups: (1) the high cholesterol fed rats were fed a high cholesterol diet containing 77% normal diet food, 3% cholesterol and 20% lard for 3 months; (2) ovariectomised (OVX) rats were bilaterally ovariectomised and fed a standard diet; and (3) the control rats were fed the standard diet. Bone mineral density (BMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 36 publications
0
64
3
Order By: Relevance
“…A recent study indicated lipid metabolic disorders with hyperlipidemia and hypercholesterolemia as a distinct risk for osteoporosis in OVX rats (Hassan and AbdelWahhab 2012). A close relation between hyper-cholesterolaemia and osteoporosis was reported, where, high cholesterol diet increases the risk of osteoporosis, through inhibiting the differentiation and proliferation of osteoblasts (You et al 2011).…”
Section: Discussionmentioning
confidence: 91%
“…A recent study indicated lipid metabolic disorders with hyperlipidemia and hypercholesterolemia as a distinct risk for osteoporosis in OVX rats (Hassan and AbdelWahhab 2012). A close relation between hyper-cholesterolaemia and osteoporosis was reported, where, high cholesterol diet increases the risk of osteoporosis, through inhibiting the differentiation and proliferation of osteoblasts (You et al 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Cholesterol and its metabolites would suppress the functional activity of osteoblasts and thereby induce reduced bone mineralization to decrease bone formation [41]. By the same token, high cholesterol diet increases the risk of osteoporosis, possible via inhibiting the differentiation and proliferation of osteoblasts in rats, as You et al observed [42]. At present, the drug treatment against osteoporosis can prevent bone loss, as well as lowering cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study on laboratory rats fed high cholesterol diets reported an increased risk for osteoporosis (You et al . ). Osteocalcin, a protein that is produced by mature osteoblasts, has an endocrine role and can affect lipid metabolism through modulation of the adipose tissue and insulin secretion.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have been performed evaluating the role of both serum and cellular cholesterol concentrations on bone health via a variety of methodologies (cell culture cell lines, animal models as well as clinical samples) in human medicine (Mandal 2015 ). The findings of these studies revealed that: (1) elevated cholesterol concentrations may increase bone turnover (You et al . 2011 );(2) treating osteoblastic cell cultures with varying concentrations of cholesterol inhibits their proliferation and differentiation (You et al .…”
Section: Introductionmentioning
confidence: 99%